The complex effect of heterogeneity and isolation in determining alpha and beta orchid diversity on islands in the Aegean archipelago. Issue 3 (2nd April 2020) - Tsiftsis, Spyros
Abstract : Knowledge of factors determining the distribution of plants on islands is of crucial importance in island biogeography. Here the drivers and mechanisms that best explain α- and β-diversity of orchids in the Aegean Archipelago were explored. The analyses were based on (a) matrix of the total number of orchid taxa recorded on each island, and (b) matrix containing the number of grid cells of each island in which each orchid has been recorded. Based on these matrices, generalized linear models (GLMs) were then used to determine the most important factors (geographical, climatic, geological) associated with orchid richness. Generalized dissimilarity modelling (GDM) was used to explore whether there are specific patterns in β-diversity and to evaluate contributions to individual factors to these patterns. To investigate the similarity of the Aegean islands in terms of their orchid flora, a β-diversity abundance matrix was analyzed using non-metric multidimensional scaling ordination method. GLM analysis revealed that maximum elevation, index of bioclimatic breadth (IBB), neighbour index (NI), island area, and the percentage of granite, limestone and quartz at each island were the best predictors of orchid α-diversity. Maximum elevation, habitat heterogeneity, IBB and island area were positively associated with α-diversity, whereas neighbour index and the percentage of granite, limestone and quartz at each island were negatively associated. Maximum elevation, NI, habitat heterogeneity and geographical distance were the best predictors of orchid turnover across the Aegean islands, whereas IBB, granite and limestone were less important. The NMDS ordination revealed that islands are structured from the southernmost to the northernmost, in a way that in general conforms to the phytogeographical division of the Aegean Archipelago. The drivers that account for the patterns in α- and β-diversity were associated with differences in the degrees of isolation and heterogeneity (climatic and habitat) of the islands. Among the predictors, elevation and IBB proved to be better surrogates of habitat heterogeneity than island area.